2009
DOI: 10.1158/1055-9965.epi-09-0166
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptor β2 Subunit (CHRNB2) Gene and Short-Term Ability to Quit Smoking in Response to Nicotine Patch

Abstract: Genes coding for nicotinic acetylcholine receptors may influence response to nicotine replacement therapy for smoking cessation. We examined the association of a 3′ untranslated region polymorphism (rs2072661) in the nicotinic acetylcholine receptor β2 subunit (CHRNB2) gene with quitting success in response to nicotine versus placebo patch during a short-term test of patch effects. In a within-subjects cross-over design, smokers of European descent (n = 156) received 21 mg nicotine and placebo patch in counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…An analysis of 417 treatment-seeking smokers from a placebo-controlled randomized clinical trial of bupropion and placebo (Lerman et al, 2006) reported significant associations with CHRNB2 SNPs rs2072660 and rs2072661 and abstinence in a logistic model incorporating main effects and interaction with treatment at the end of treatment (P ¼ 0.01) and at 6 months (P ¼ 0.0002) (Conti et al, 2008). A short-term test of nicotine vs placebo patch effects in 156 smokers reported a significant association between rs2072661 and the number of abstinent days (Perkins et al, 2009). In an analysis of CHRNA4 and CHRNB2 SNPs in a sample of 1068 older adolescents, rs2072660 was reported to be significantly associated with sensitivity to tobacco (subjective effects of 'nauseous' or 'dizzy') (Ehringer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of 417 treatment-seeking smokers from a placebo-controlled randomized clinical trial of bupropion and placebo (Lerman et al, 2006) reported significant associations with CHRNB2 SNPs rs2072660 and rs2072661 and abstinence in a logistic model incorporating main effects and interaction with treatment at the end of treatment (P ¼ 0.01) and at 6 months (P ¼ 0.0002) (Conti et al, 2008). A short-term test of nicotine vs placebo patch effects in 156 smokers reported a significant association between rs2072661 and the number of abstinent days (Perkins et al, 2009). In an analysis of CHRNA4 and CHRNB2 SNPs in a sample of 1068 older adolescents, rs2072660 was reported to be significantly associated with sensitivity to tobacco (subjective effects of 'nauseous' or 'dizzy') (Ehringer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Gene-gene interactions are reported between DRD2 Taq1A- SLC6A3 VNTR [40] and DRD2 Taq1A- CYP2B6 C1459T [47]. The variant CHRNB2 rs2072661, which encodes for a nicotinic receptor is associated with SC [51,52]. However, this finding is not replicated in the study of Spruell et al [53].…”
Section: Resultsmentioning
confidence: 99%
“…Some gene-treatment interactions have been reported in European ancestries. Interactions with nicotine replacement therapy are observed for OPRM1 A118G [36], DRD4 VNTR [48], COMT Val 108/158 Met [43], CHRNB2 rs2072661 [52], and GALR1 rs2717162 [55]. Bupropion interacts with SLC6A4 5-HTTLPR [34], DRD2 TaqIA [42,47], DRD2- 141C [41], DRD4 VNTR [45], CYP2B6 *6 [120], and GALR1 rs2717162 [55].…”
Section: Resultsmentioning
confidence: 99%
“…There are some positive findings with rs2072661, which is in strong linkage with rs2072660 in association with smoking behavior. Perkins et al (2009) found that rs2072661 was associated with a greater number of days of nicotine abstinence during patch therapy. In a gene-gene interaction study, rs2072661 had a significant effect on FTND in interaction with CHRNA4 and NTRK2 genes .…”
Section: Total Population Males Femalesmentioning
confidence: 95%